Психолингвистический аспект рассмотрения текста в системе обучения РКИ - Митина, Светлана (Studia Rossica Posnaniensia, 2015)
This article investigates an important issue, i.e. the specifics of teaching the analysis of a text which is the product of non-native speakers’ speech activity. A text is treated as an object of a complex nature, and special attention is given to its fundamental linguistic and psycholinguistic characteristics. The proposed method for teaching text analysis and construction is based on a psycholinguistic approach toward the problem of constructing oral and written texts.